Hardware Interaction using Hand Gestures - Jain, K. A; Mishra, P; Arora, L; Kotian, M.S (International Journal of Computer Sciences and Engineering, 2025)
Gesture recognition is a mode for computers to begin to comprehend human body language, thus structuring a better-off channel between machines and humans than primitive text user interfaces or even GUIs. It enables humans to communicate with the machine and interact naturally without any intervention of mechanical devices. This technology not only saves time to unlock or operate any device but also makes human-computer interaction natural. The focus of this paper is on building a hand gesture recognition device using image processing for controlling the appliances by simple hand gestures instead of using any remote control devices or switches, thereby making user interaction as natural as possible. This is achieved by building a robotic arm using leap motion, Arduino UNO and different types of motors.